INTEGRATING THE SHADOW ECONOMY INTO THE FORMAL SECTOR THROUGH FINANCIAL MECHANISMS (Spectrum Journal of Innovation, Reforms and Development, 2024)
The shadow economy in Uzbekistan plays a significant role in affecting macroeconomic stability, reducing the tax base, and hindering entrepreneurial growth. This article examines financial strategies designed to formalize the shadow sector, such as tax system reforms, streamlined financial reporting, encouragement of digitalization, and automation of processes. Emphasis is placed on leveraging international practices and adapting them to Uzbekistan's specific circumstances. The study provides recommendations to mitigate the adverse impacts of the shadow economy on the country's economic development.